Assessing the Effects of Surface Conditions on Potential Evapotranspiration in a Humid Subtropical Region of China - Wang, Hailong; Zheng, Jinghua (Frontiers in Climate, 2022)
The ability of the atmosphere to remove water from land surface is measured by potential evapotranspiration (ETp), which is often inferred by the reference evapotranspiration (ETo). Therefore, ETp is often considered only influenced by the above-ground meteorological conditions. Based on its concept, ETp should also link with surface conditions that influence the surface resistance. Such linkages differ in dry and wet regions with different surface covers. Here, we calculated ETo and especially analyzed the effects of surface conditions including vegetation cover indicated by NDVI (Normalized Difference Vegetation Index) and root-zone SWC (soil water content) in a humid subtropical province of China. Results show that ETp, NDVI, wind speed, temperatures have increased significantly during 1982-2015 and relative humidity (RH) has decreased significantly. Linear trends of these variables varied across seasons, but similarities were found between spring and winter and between summer and autumn. Summer saw the greatest changes in ETp per unit of environmental variable change. Solar radiation, RH and precipitation exerted overall stronger influence on ETp (R2>0.50) than other factors. NDVI and SWC were found positively and negatively affecting ETp at all time scales. Partial correlation analysis showed significant influence of NDVI and SWC at the monthly scale; moreover, SWC influenced ETp more significantly in summer than other seasons (p<0.05). Since actual evapotranspiration is often deducted from ETp by multiplicative stress functions in many hydrologic models, understanding the relationships between ETp and environmental changes can help improve the formulation and estimation of actual evapotranspiration.